Mortality Baseline Model Using Linear Time Series and Linear Mixed Model in Excess Mortality Calculation During COVID-19 in DKI Jakarta - Agistia, Maulia Dita; Suardi, Lenny (Universitas Negeri Surabaya, 2023)
COVID-19 pandemic has affected the mortality across a globe. To investigate the impact of COVID-19, many countries have recorded number of deaths due to COVID-19. In Indonesia, DKI Jakarta reports the highest number of mortality due to COVID-19. However, the reported data may have discrepancy, for example the scope of testing for COVID-19 that has not been widely implemented, false-negative on testing results and deaths that occur before COVID-19 test. The measurement of excess mortality has been suggested to cover the lack of data. Baseline mortality will be the main component in calculating excess mortality. Monthly deaths data of DKI Jakarta from January 2018 up to February 2021 will be used to generate baseline mortality model. The analysis will compare two models, linear time series and linear mixed model. Model accuracy will be calculated to choose the better baseline mortality model. The better model of baseline mortality will give better estimation of excess mortality during COVID-19. Linear time series provides a better accuracy on baseline mortality model in DKI Jakarta. The result shows that there are 25,553 excess mortality during COVID-19 pandemic in DKI Jakarta from June 2020 until June 2021. The SMR during pandemic COVID-19 is around 133%.